Secretion Of PGC-1α By Modulating Physical Exercise To Protect Improving Obesity Prevalence - Moch Nasmay Lupita; Desiana Merawati; Sugiharto Sugiharto (Universitas STRADA Indonesia, 2020)
This study aims to analyze the response of physical exercise as a modulation of PGC-1α to protect against the increasing prevalence of obesity. This research is a true experimental design with the randomized pretest-posttest control group design using 15 obese women aged 18-22 years, Body Mass Index (BMI) 25-35 kg/m2, normal blood pressure, Resting Heart Rate (RHR) normal, VO2max 25-35 ml/kg/min and randomly divided into three groups, namely CONT (n=5, Control Without Intervention), MIIE (n=5, Moderate Intensity Interval Exercise) and MICE (n=5, Moderate Intensity Continuous Exercise). The intervention was carried out at 07.00-09.00 a.m. MIIE and MICE interventions carried out for 40-45 minutes using a treadmill. Pre-exercise blood sampling and 10 minutes post-exercise. Measurement of PGC-1α levels used the Enzyme-Linked Immunosorbent Assay (ELISA) method. Data analysis techniques used ANOVA test and LSD post hoc test with the Statistical Package for Social Science (SPSS)